Angular analysis and branching fraction measurement of the decay B-0 -> K*(0)mu(+)mu(-) - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Eroe, J; Fabjan, C; Friedl, M; Fruehwirth, R; Ghete, V; et al. (2013)
The angular distributions and the differential branching fraction of the decay B0→K*(892)0μ+μ- are studied using a data sample corresponding to an integrated luminosity of 5.2fb-1 collected with the CMS detector at the LHC in pp collisions at s=7TeV. From more than 400 signal decays, the forward-backward asymmetry of the muons, the K*(892)0 longitudinal polarization fraction, and the differential branching fraction are determined as a function of the square of the dimuon invariant mass. The measurements are in good agreement with standard model predictions. © 2013 CERN.